2020
DOI: 10.1021/acsomega.0c03020
|View full text |Cite
|
Sign up to set email alerts
|

Production, Collection, and Purification of 47Ca for the Generation of 47Sc through Isotope Harvesting at the National Superconducting Cyclotron Laboratory

Abstract: An experiment was performed at the National Superconducting Cyclotron Laboratory using a 140 MeV/nucleon 48 Ca beam and a flowing-water target to produce 47 Ca for the first time with this production route. A production rate of 0.020 ± 0.004 47 Ca nuclei per incoming beam particle was measured. An isotope harvesting system attached to the target was used to collect radioactive cationic products, including 47 Ca, from the water on a cation-exchange resin. The 47 Ca collected was purified using three separation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…It is also possible to produce 47 Sc via the beta decay of 47 Ca. To do this, 47 Ca is generally produced via photon or proton irradiation of 48 Ca [24,25], neutron irradiation of 46 Ca [24,26], or fragmentation of a 48 Ca beam in water [27].…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to produce 47 Sc via the beta decay of 47 Ca. To do this, 47 Ca is generally produced via photon or proton irradiation of 48 Ca [24,25], neutron irradiation of 46 Ca [24,26], or fragmentation of a 48 Ca beam in water [27].…”
Section: Introductionmentioning
confidence: 99%
“…With the 70 MeV proton cyclotron installed at the INFN-LNL, the research activities carried out within Laboratory of Radionuclides for Medicine (LARAMED) are focused on the production of emerging radionuclides with proton beams [ 2 ]. Among the radionuclides of major interest for our team is 47 Sc, a theranostic radionuclide that presents suitable decay characteristics for SPECT imaging and β − therapy ( Table 1 ), which can be also paired with the β + emitter counterparts 43 Sc and 44 Sc for PET applications [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The lack of 47 Sc production is limiting its use in preclinical and clinical trials; for this reason, the 47 Sc proton-based production routes have been investigated within the PASTA and REMIX projects [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated the therapeutic suitability of 47 Sc with the diagnostic analogue 44 Sc [1,2,3]. In practice there are almost more than 10 reactions are reported to produce 47 Sc which includes using both reactors and accelerators [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37] and by taking Ti, V or Ca as target materials. When it comes to accelerators, cyclotrons with proton beams are available in large numbers compared to other charged particle accelerator facilities.…”
Section: Introductionmentioning
confidence: 99%